Law enforcement toward better marine fisheries governance in China - Jiang, Qi; Sun, Kangjie (Frontiers in Marine Science, 2025)
This paper examines introduces China's marine fishery enforcement and judicial practices, highlights China's solutions and efforts in protecting marine fisheries. Currently, the profits of China's marine fisheries industry have continued to decline, and the economic development of the fisheries sector faces significant challenges. Through literature research and case analysis methods, this paper analyzes the theoretical guidance of good ocean governance for marine fisheries protection. Focusing on legislative, enforcement, and judicial dimensions of governance, it explores the problems in current legal regulation for marine fisheries protection and the practice of marine fisheries conservation in China. This study concludes that the eight elements of good ocean governance theory provide a theoretical framework for international and national marine fisheries protection through the logics of rules-based constraints, multi-stakeholder governance, and adaptive flexibility. Strong legal enforcement is essential for ensuring healthy and sustainable marine fisheries development.